2021
DOI: 10.3389/fnmol.2021.616886
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Selective Inhibition of Histone Deacetylase 1 and 3 in Huntington’s Disease Mice

Abstract: Huntington’s disease (HD) is an autosomal dominant neurodegenerative disease characterized by a late clinical onset of psychiatric, cognitive, and motor symptoms. Transcriptional dysregulation is an early and central disease mechanism which is accompanied by epigenetic alterations in HD. Previous studies demonstrated that targeting transcriptional changes by inhibition of histone deacetylases (HDACs), especially the class I HDACs, provides therapeutic effects. Yet, their exact mechanisms of action and the feat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“…The disturbed acetylation balance and consequent dysregulation of gene expression caused by the loss of function of specific HATs are thought to be responsible for some of the detrimental cellular effects observed in HD pathogenesis. This hypothesis is supported by experiments demonstrating that increasing the level of specific HATs [ 20 , 31 , 32 ] or inhibiting the histone deacetylase activity can alleviate mHtt-induced symptoms [ 33 , 34 , 35 ], supposedly by restoring the acetylation balance and transcriptional regulation. It is still not known, however, which histone acetylation sites are most important in terms of HD pathogenesis and possible therapeutical applications.…”
Section: Discussionmentioning
confidence: 88%
“…The disturbed acetylation balance and consequent dysregulation of gene expression caused by the loss of function of specific HATs are thought to be responsible for some of the detrimental cellular effects observed in HD pathogenesis. This hypothesis is supported by experiments demonstrating that increasing the level of specific HATs [ 20 , 31 , 32 ] or inhibiting the histone deacetylase activity can alleviate mHtt-induced symptoms [ 33 , 34 , 35 ], supposedly by restoring the acetylation balance and transcriptional regulation. It is still not known, however, which histone acetylation sites are most important in terms of HD pathogenesis and possible therapeutical applications.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, recent studies indicate that HDAC3 expression promotes neurodegenerative diseases such as PD, AD and HD. In the case of HD and AD, further in vitro and in vivo studies confirmed these data, underling that HDAC3′s inhibition protected from cognitive decline [ 17 , 42 ].…”
Section: Hdac Inhibitors (Hdacis)mentioning
confidence: 88%
“…The identification of an anti-tumor agent without a neurotoxic activity or even with neuroprotective properties, to be used alone or in combination, could dramatically impact anticancer treatment. So far, several papers investigated the antineoplastic potential of HDACis [ 16 , 17 , 18 , 19 ], and in this review we want to spotlight their activity on the nervous system. To better understand the potential of such molecules for the treatment of neurological diseases (including those of toxic origin, such as chemotherapy-induced peripheral neurotoxicity), we present an overview of the different HDACs and their putative role in neuronal and glial cells.…”
Section: Hdac Inhibitors (Hdacis)mentioning
confidence: 99%
“…These changes were linked to altered activities of certain transcription factors in HD (Ng et al, 2013;Vashishtha et al, 2013;Consortium, 2017). Importantly, genetic and pharmacological approaches that target epigenetic changes to correct aberrant transcription were shown to ameliorate HD features in preclinical trials (Ferrante et al, 2003;Thomas et al, 2008;Vashishtha et al, 2013;Suelves et al, 2017;Yildirim et al, 2019;Hecklau et al, 2021), validating the central role of transcriptional dysregulation in HD pathogenesis. Collectively, others and we demonstrated aberrant expression of thousands of genes and the associated changes in epigenomic profiles and regulatory factor activities in cell and animal models of HD and in HD patients; however, a systematic review comprising all the transcriptional profiling studies in HD is still lacking.…”
Section: Introductionmentioning
confidence: 91%